The Contribution of Environmental Strategies, Entrepreneurial Innovation and Entrepreneurial Orientation in Enhancing Firm Environmental Performance and Energy Efficiency - Khalid, Nadeem; Salykova, Leila; Capar, Nejat (International Journal of Energy Economics and Policy, 2020)
The objective of the current study is to empirically investigate the link between entrepreneurial attributes, strategic capabilities, and environmental nexus in Malaysian manufacturing firms. In doing so, the present study is motivated to recognize the role of entrepreneurial innovation, entrepreneurial orientation and environmental strategies in influencing firm's energy efficiency potential and environmental performance. To the best of our knowledge, the current study is first of its kind in investigating the effect of the considered explanatory variables on energy efficiency. Moreover, in line with the rising emphasis on environmental impact of firms, the current study is novel for identifying the relationship of firm's internal expertise and capabilities in leading environmental performance. The data is collected from different multinational firms in Malaysia. We applied PLS-SEM on the 300 samples which suggested that environmental strategy, entrepreneurial innovation, and entrepreneurial orientation have a positive and significantly influenced environmental performance and energy efficiency. Technical speaking, the results confirm that the environmental strategy, entrepreneurial innovation, and entrepreneurial orientation are the key contributors to enhance the energy efficiency and environmental performance of multinational firms in Malaysia. Keywords: Environmental strategy, entrepreneurial innovation, firm performance, energy efficiency, Malaysia JEL Classifications: L26, E01, L25 DOI: https://doi.org/10.32479/ijeep.9226